2015
DOI: 10.1002/ppap.201400065
|View full text |Cite
|
Sign up to set email alerts
|

Nanocomposites Prepared with High Density Polyethylene and Carbon Nanofibers Modified by Ethylene Plasma

Abstract: Carbon nanofibers (CNFs) are surface-modified by plasma polymerization using ethylene as monomer. The modified CNFs are suitable to be mixed with different polyethylenes. In this study, we mix them with high density polyethylene (HDPE). The plasma-coated CNFs (pCNFs) are then characterized by Infrared Spectroscopy (FTIR), Thermogravimetric Analysis (TGA), and Scanning Electron Microscopy (SEM) in the transmission mode (STEM). Treated and untreated CNFs are evaluated in water, chloroform, and 1,2,3-trichloroben… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 29 publications
3
5
0
Order By: Relevance
“…This study is expected to see an increase in interaction between the nanoclay modified with plasma and the matrix, when of both phases are the same. In previous studies, this polymeric coating has already been confirmed on other different nanomaterials using plasma polymerization [5,15,39].…”
Section: Characterization Of Nanoclaysupporting
confidence: 62%
See 3 more Smart Citations
“…This study is expected to see an increase in interaction between the nanoclay modified with plasma and the matrix, when of both phases are the same. In previous studies, this polymeric coating has already been confirmed on other different nanomaterials using plasma polymerization [5,15,39].…”
Section: Characterization Of Nanoclaysupporting
confidence: 62%
“…In samples of PS/Na + -MMT/MMA and PS/Na + -MMT/St nanocomposites, the results indicate that there is no evidence of a significant level of exfoliation or intercalation of Na + -MMT modified by plasma in the PS/Na + -MMT nanocomposites, possibly because the coating formed by plasma on the nanoclay does not allow the introduction of the St or MMA polymer in-between the nanoclay galleries. This, however, does not contradict the surface interaction results demonstrated by the article which are attributed to the compatibility of the coating of the nanoclay Na + -MMT/St with the PS matrix, as well as the shear stress during melt mixing [39].…”
Section: Characterization Of Polymer Nanocompositessupporting
confidence: 42%
See 2 more Smart Citations
“…To this end, surfactants, mechanical mixing, or surface modifications have been proposed . For CNF surface functionalization, several methods like acid oxidative solution, compatibilizer addition, thermal oxidation, plasma coating, and plasma oxidation have been proposed.…”
Section: Introductionmentioning
confidence: 99%